Теоретичні проблеми вивчення давньої історії України - Толочко, П.П. (Археологія, 2005)
У статті йдеться про актуальні теоретичні проблеми вивчення давньої історії України. В статье подвергнуты анализу методологические подходы в исследовании древней истории Украины. В советское время, как известно, в этой области господствовало марксистское учение, главный смысл которого сводился к жесткому формационному эволюционизму. Ныне оно подвергается критике, часто не вполне справедливой. Если иметь в виду археологическую периодизацию, то она, по существу, основывается на тех же базисных принципах, что и марксистская историческая периодизация. Автор убежден, что компетенцией археологической науки является не только изучение следов человеческой деятельности, но и реконструкция исторического процесса. Чрезвычайно важной представляется проблема этнокультурного развития древнего населения Украины. Процессы эти были сложными и многолинейными. Их нельзя свести к простому биологическому воспроизводству одного и того же населения на одной и той же территории. Поэтому не следует искать для современного украинца тождественного его этнографической ипостаси народа в глубокой древности. Во все времена территория нынешней Украины была контактной зоной, где встречались народы и культуры Востока и Запада. В отдельные периоды соединение традиций Востока и Запада приводило здесь к необычайному взлету культурной жизни. Methodological approaches to the study of the ancient history of Ukraine have been analyzed in the article article. As it is well known, in Soviet period the Marxism doctrine was dominant in this sphere. The main idea of this doctrine added up to strict formational evolutionism. It is much criticized at present, often not justly. If we consider archaeological periodization, it essentially rests upon the same basic phenomena as the Marxism historical periodization. The author is convinced that the terms of reference of the archaeological science cover not only the traces of human activity, but also the reconstruction of the historical process. The problem of ethnocultural development of the ancient population of Ukraine appears utterly important. These processes were complex and multilineal. They should not be reduced to simple biological reproduction of the same population on the same territory. For this reason one should not look for an ethnographical hypostasis identical to the modern Ukrainians in the distant antiquity. The territory of the present-day Ukraine at all times was a contact area where peoples and cultures of Orient and West were meeting. In some periods integration of Oriental and Western traditions resulted in extraordinary peaks in cultural life here.